ASHABIYAH IBNU KHALDUN DAN RELEVANSINYA DENGAN NASIONALISME DI INDONESIA - Hanna Widayani (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2017)
The problem in this research is how ‘Ashabiyah Ibn Khaldun and how’ ashabiyah Ibn Khaldun and its relevance to nationalism in Indonesia.The purpose of this research is to describe the concept of ‘Ashabiyah Ibn Khaldun and describes how its relevance to Indonesian nationalism. The type of this research is library research and the method used in this research is descriptive qualitative. The results of this research are, first; ‘Ashabiyah is defined by Ibn Khaldun as social solidarity. According to Ibn Khaldun social solidarity or a sense of class connected by blood relation or other linkage that has the same meaning and purpose. This is because blood ties have a binding force in most humans, which makes them feel the pain that affects them. Ashabiyya is a feeling of one group or social solidarity, which arises naturally in human life due to a blood relation or revelation affinity. Such feelings of love give rise to a sense of destiny, mutuality, mutual loyalty, mutual need, especially when faced with calamities or threats of the enemy, or to achieve certain goals. Then Ibn Khaldun argues that it is impossible to create a state without the support of a strong sense of unity and solidarity. The process of its founding requires a real struggle, a battle of life and death. Solidarity (‘asabiya) is principally co-operation and please help the group closely in such a way that the members of each group are not only assisting but willing to sacrifice life for the common good. And this according to him is a natural phenomenon for humans in the process of the establishment of the state. Second; The relevance or relationship between ‘Ashabiyah Ibn Khaldun/ social solidarity with Indonesian nationalism in modern times is, lies in its components. Which in the ‘Ashabiyah, Ibn Khaldun positioned the society or nation as a starting point to build a state, which then in truth the community both have a high spirit to fight for the ideals of the nation and state. Because the goal of Indonesian nationalism itself is nothing but to arouse the sense of brotherhood / kinship in the Indonesian nation, and always keep the national identity as a form of the love of the nation and the country.